2012
DOI: 10.1021/jp3045324
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of the Roles of Na+and Water on the Adsorption of Formamide on Kaolinite Surfaces

Abstract: The adsorption of formamide (FA) on kaolinite surfaces and the roles of Na + and water on the adsorption were investigated theoretically using a density functional theory. The calculations reveal that adsorbed FA is able to form stable complexes with the tetrahedral and octahedral surfaces of kaolinite. The octahedral surface possesses a larger binding affinity toward FA than the tetrahedral site of kaolinite partially due to the presence of the surface hydroxyl groups that are more active in the intermolecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 63 publications
3
17
0
Order By: Relevance
“…Several computational works on this topic have already been referenced and summarized in [81]. Some of them were focused on the interaction of formamide (NH 2 CHO, FA) with dickite [117,118] and kaolinite [119,120] surface models, which were simulated adopting cluster approaches. In the cases where no isomorphic substitutions were performed, the driving forces for the interaction were dictated essentially by H-bonding.…”
Section: In Silico Prebiotic Studies On Mineral–organic Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several computational works on this topic have already been referenced and summarized in [81]. Some of them were focused on the interaction of formamide (NH 2 CHO, FA) with dickite [117,118] and kaolinite [119,120] surface models, which were simulated adopting cluster approaches. In the cases where no isomorphic substitutions were performed, the driving forces for the interaction were dictated essentially by H-bonding.…”
Section: In Silico Prebiotic Studies On Mineral–organic Interactionsmentioning
confidence: 99%
“…However, it is worth mentioning that such a comparison could be biased by the excess of flexibility of the cluster models in the intercalation region. On the kaolinite surfaces [119,120], calculated adsorption energies of FA on the non-hydrated octahedral and tetrahedral sheets were found to be −14.8 kcal mol −1 and −13.7 kcal mol −1 (see Table 1). Simulated IR spectra of FA interacting with kaolinite surfaces were compared with the experimental one [120], which served to conclude that FA indeed interacts through H-bonds, particularly between the Al−OH octahedral kaolinite face and the FA C=O group (see Figure 3A).…”
Section: In Silico Prebiotic Studies On Mineral–organic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is also supported by the theoretical study of the interactions of formamide with kaolinite and dickite surfaces. 2729 The experimental studies of formamide intercalated in kaolinite and dickite also suggested that the carbonyl oxygen atom forms almost three H-bonds with the hydroxyl groups on the octahedral surface. 17,19,20 The RDF peaks of hydrogen atoms in HC═O groups and NH groups of formamide with basal oxygens on the tetrahedral surface are less well-defined (Figure 6), suggesting the relatively weaker interactions between them.…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of nucleobases over surface of several clays was often described the at density functional theory (DFT) level [48]. The modeling of kaolinite by the Leszczynski team [49,50] underscored the role of calcium for the adsorption of formamide over the clay’s surface. Bhushan et al reported manganese oxides as a possible catalyst for the nucleobase synthesis [1].…”
Section: Introductionmentioning
confidence: 99%